The idea of history - Collingwood,R.G. (NewDelhi : Aakar, 2021)
The Idea of History (1946) is a book of philosophy that explores the nature of history and the historian's interpretation of it. Written by English historian, archaeologist, and philosopher R.G. Collingwood, the work encourages students of history to go beyond events into the motivations of the actors themselves. R.G. Collingwood (b. 1889, d. 1943) was the son of an artist/archaeologist father and artist/pianist mother. Showing an aptitude for the classics and history from an early age, he was recognized at school in Classic Moderations (representing fluency in Greek and Latin) as well as ancient history and philosophy. He soon entered academia and spent his entire professional life at Oxford. In fact, he was elected a fellow of Pembroke College, Oxford before he even graduated from University College. Later, he became the Waynflete Professor of Metaphysical Philosophy at the Magdalen College, Oxford. While his teaching work focused on philosophy, he was also a well-known archaeologist, spending his school vacations on dig sites like Hadrian's Wall and writing scholarly articles and books. These works include The Archaeology of Roman Britain (1930) and Roman Britain and the English Settlements, the first volume of the Oxford History of England (1936). Collingwood was considered the leading authority on Roman Britain during his lifetime. Collingwood died in 1943, after several strokes. In the following years, his student T. M. Knox collected a series of lectures by Collingwood, primarily written in 1936, and published them as The Idea of History in 1946. The book is split into five parts, spanning views of history from Herodotus in the Greco-Roman times through the advent and ascendency of Christianity, the Enlightenment, and the 19th Century. Collingwood considered history a science of human affairs mingled with psychology. He argues that to understand the past, the historian must use their "historical imagination" to recreate the thought process of the actors. By reliving the past in their own mind, the historian can discover the significant patterns and dynamics of previous civilizations. From a focus on humanism in the Greco-Roman era, to a theocentric view in Medieval times, to a reliance on science and a more "mature" worldview in the Enlightenment and beyond, Collingwood explores how the historians and philosophers in each time viewed history, and how their worldviews influenced their own perceptions of the past. It is only through the medium of the historian's mind, he argues, that historical facts can be interpreted. By immersing ourselves in the mentality of history's actors, we can rethink the past with a better understanding of the thoughts and motivations that guided their actions. Through the development of this historical consciousness, we can both understand the past and our place in the present world. But we must be careful not to impose our own values and beliefs onto these past actors, skewing their thoughts with our own. To do so leads to "scissors-and-paste" narratives of history, where sources are believable only if they suit the historian's own frame of mind. While the opinions expressed in The Idea of History are not shared by all historians, the work is nevertheless an important contribution to historical philosophy. His ideas were particularly central to historical debate during the 1950s and 1960s, and books have been written to support or refute his philosophy of history. He has influenced many great thinkers through the latter half of the 20th century and into the present.
1.greco roman historiography 2.the influence of christianity 3.the threshold of scientific history 4.scientific history 5.epilegomena.
Includes index.
Keywords: History; History philosophy